Improving rural livelihoods and minimizing land degradation through the community watershed approach for sustainable development of dryland areas - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Through networking of partners by way of a consortium approach, the project has demonstrated that 50% of chemical fertilizers can be substituted with the locally-produced vermicompost that the farmers themselves make. In Madhya Pradesh 800 trials were conducted, and a 1000 in Rajasthan, during the post-rainy season, which demonstrated the productivity benefits that can be achieved by following the science-led farmer participatory approach. Scaling-out the benefits of productivity enhancement and community watershed management is done with technical backstopping in the target agro-eco-regions of Madhya Pradesh (9 districts) and Rajasthan (7 districts) along with carrying out capacity-building of lead farmers, development workers, and consortium partners.